2019
DOI: 10.1371/journal.pone.0211578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and dosimetric study of hypofractionated Helical TomoTherapy in breast cancer patients

Abstract: We present a single center’s experience of treatment outcomes and dosimetric parameters for breast cancer patients treated with hypofractionated Helical TomoTherapy (HT). This is a retrospective study of one hundred and thirty-six patients with invasive breast cancer treated between March 2012 and October 2016. Dosimetric parameters and 3-year loco-regional failure free survival (LRFFS) were analyzed. Dose to ipsilateral lung, heart and contralateral breast as well as acute and late toxicities were recorded. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In delivering a prescribed radiation dose to a well-defined target, the imperative (that of the International Commission on Radiological Units, ICRU) [ 1 ] is to achieve accuracy to within < 5% while at the same time minimizing dose to surrounding healthy tissue, a matter discussed in detail by Kry et al (2017) [ 2 ]. It has become much more complex to manage the dosimetry of the novel techniques of advancing radiotherapy including small and microbeam therapies [ 3 – 4 ], hypo-fractionation [ 5 ]and FLASH radiotherapy [ 6 ]. This is due to the various influencing factors which necessarily effect the ability to achieve such accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…In delivering a prescribed radiation dose to a well-defined target, the imperative (that of the International Commission on Radiological Units, ICRU) [ 1 ] is to achieve accuracy to within < 5% while at the same time minimizing dose to surrounding healthy tissue, a matter discussed in detail by Kry et al (2017) [ 2 ]. It has become much more complex to manage the dosimetry of the novel techniques of advancing radiotherapy including small and microbeam therapies [ 3 – 4 ], hypo-fractionation [ 5 ]and FLASH radiotherapy [ 6 ]. This is due to the various influencing factors which necessarily effect the ability to achieve such accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…depth and posterior x‐ray field prescribed point at midline depth was used for axillary nodes combined with anterior electrons to treat internal mammary nodes. Subsequently, helical tomotherapy (HT) often becomes the treatment of choice for PMRT due to improved conformality to the target, while sparing the OARs 2 …”
Section: Introductionmentioning
confidence: 99%
“…The CI value is typically 0–1, and the closer it is to 1, the better the conformability of the PTV. A larger HI represents worse PTV heterogeneity ( 21 , 22 ). The present study results showed that compared with intensity-modulated radiotherapy, TOMO produced a significant improvement in dose conformity (0.82±0.0327 vs. 0.75±0.064, respectively; P=0.006) and homogeneity (1.03±0.006 vs. 1.09±0.076, respectively; P<0.001).…”
Section: Discussionmentioning
confidence: 99%